2021
DOI: 10.1038/s41467-021-20935-9
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment neutrophil-to-lymphocyte ratio and mutational burden as biomarkers of tumor response to immune checkpoint inhibitors

Abstract: Treatment with immune checkpoint inhibitors (ICI) has demonstrated clinical benefit for a wide range of cancer types. Because only a subset of patients experience clinical benefit, there is a strong need for biomarkers that are easily accessible across diverse practice settings. Here, in a retrospective cohort study of 1714 patients with 16 different cancer types treated with ICI, we show that higher neutrophil-to-lymphocyte ratio (NLR) is significantly associated with poorer overall and progression-free survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
238
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 285 publications
(252 citation statements)
references
References 57 publications
12
238
1
1
Order By: Relevance
“…This suggests that increased neutrophils counts in the peripheral blood were associated with less benefit from ICI. Another retrospective cohort study with 1714 patients examined the association between pretreatment NLR and TMB levels and survival among patients treated with ICI, and found that the patients with NLR-high/TMB-low had the worst prognosis, while those in the NLR-low/TMB-high group had the best prognosis (23). Other studies also found that patients with advanced NSCLC receiving immunotherapy with high NLR or PLR value (i.e., markers of chronic inflammation) usually showed poor prognosis (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that increased neutrophils counts in the peripheral blood were associated with less benefit from ICI. Another retrospective cohort study with 1714 patients examined the association between pretreatment NLR and TMB levels and survival among patients treated with ICI, and found that the patients with NLR-high/TMB-low had the worst prognosis, while those in the NLR-low/TMB-high group had the best prognosis (23). Other studies also found that patients with advanced NSCLC receiving immunotherapy with high NLR or PLR value (i.e., markers of chronic inflammation) usually showed poor prognosis (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, immunotherapy based on immune checkpoint inhibitors has been successful in treating NSCLC, especially in patients with a high tumour mutation burden (TMB), CD8 + tumour cell infiltration, and programmed death-ligand 1 (PD-L1) expression (14). In a retrospective study, Valero et al showed that neutrophil-to-lymphocyte ratio (NLR) is a suitable and promising biomarker for immunotherapy (15). They suggested that higher NLR is associated with poor prognosis after immune checkpoint inhibitors (ICI) therapy.…”
Section: Progress In Immunotherapy Of Kras-mutant Nsclcmentioning
confidence: 99%
“…In a retrospective study, Valero et al. showed that neutrophil-to-lymphocyte ratio (NLR) is a suitable and promising biomarker for immunotherapy ( 15 ). They suggested that higher NLR is associated with poor prognosis after immune checkpoint inhibitors (ICI) therapy.…”
Section: Progress In Immunotherapy Of Kras-mutant Nsclcmentioning
confidence: 99%
“…To study this hypothesis, we first collated the largest publicly available cohort of ICItreated (anti-PD1/anti-PDL1) patient's responses with TMB and demographic information, comprising 1959 patients [4,5,7,8] together with an additional new cohort of 318 patients, comprising a total of 2277 patients across 14 cancer types. Analyzing this combined cohort, we first aimed to depict the association between TMB-H and patients' response to ICI in each cancer type.…”
Section: Mainmentioning
confidence: 99%